Cbl‐family proteins as regulators of cytoskeleton‐dependent phenomena. Issue 12 (23rd August 2013) - Lee, Hojin; Tsygankov, Alexander Y.
ABSTRACT Although the role of Cbl‐family proteins as key cellular regulators has been established, phenomena regulated in a Cbl‐dependent fashion are multiple and the mechanisms mediating the effects of Cbl proteins are diverse. This finding makes it important to consider different phenomena affected by functions of Cbl proteins individually. Among effects of Cbl on various biological functions there are many cases of regulation of cellular phenomena related to cytoskeletal rearrangements, such as cell adhesion, motility and invasion. Some of these regulatory functions are mediated by adaptor‐type interactions of Cbl, especially by Cbl‐dependent modulation of phosphatidyl‐inositol‐3′ kinase (PI3K), while others are caused by Cbl‐dependent ubiquitylation of various cytoskeletal and regulatory proteins, identified and unidentified. The role of Cbl in regulation of cytoskeleton‐dependent cellular functions is discussed in this review. J. Cell. Physiol. 228: 2285–2293, 2013. © 2013 Wiley Periodicals, Inc.